Uncovering Customer Reuse Intention on Coffee Shop Mobile Application: Is That Impactful? - Gon, Kim Gwi; Pidada, Ida Ayu Iswari (Jurnal Ilmiah Manajemen & Bisnis, 2024)
This study aims to explore the factors influencing customer behavior by examining the reuse intention of mobile applications, specifically focusing on Fore Coffee’s customers. Utilizing the Technology Acceptance Model (TAM), the research investigates how perceived usefulness, perceived ease of use, and perceived value impact the intention to reuse the Fore Coffee mobile application. Data were gathered through a survey of Fore Coffee customers in Bali, employing non-probability sampling techniques, with purposive sampling as the specific method. The analysis was conducted using multiple linear regression analysis via SPSS software to determine the relationships between the independent variables (perceived usefulness, perceived ease of use, and perceived value) and the dependent variable (reuse intention). The findings reveal that perceived value does not significantly affect the intention to reuse the Fore Coffee mobile application. In contrast, perceived usefulness and perceived ease of use both have a partially significant positive impact on the reuse intention. These results suggest that while the perceived value of the app might not directly influence customers' decision to continue using it, factors such as its usefulness and ease of use play crucial roles in fostering reuse intentions. This insight is valuable for app developers and marketers aiming to enhance customer retention through improved user experience and functionality.